Integrating Ethno-Vlog into Liveworksheet-Based E-LKPD: Developing Contextual Ecology Learning Media to Enhance Students’ Science Literacy - Azqia Noviatun Nisa; Sudarmin; Risa Dwita Hardianti; Hendra Febriyanto; Fredy Supriadi (ISEJ : Indonesian Science Education Journal, 2024)
The low level of Indonesian students’ science literacy as reflected in the PISA 2022 results highlights the need for innovative, contextualized learning media that can bridge scientific concepts with real-life and cultural experiences. This study aimed to develop and evaluate a Liveworksheet-integrated E-LKPD enriched with an ethno-vlog of Bukit Manengteung on ecology and ecosystem material to enhance students’ science literacy. Employing a research and development design with the 4D model (define, design, develop, and disseminate), the product was validated by experts, tested for readability, and implemented with seventh-grade students at SMP Negeri 2 Ciledug during the 2024/2025 academic year. Validation results indicated high feasibility with Aiken’s V values above 0.87, while student responses confirmed that the media was engaging, clear, and easy to use. Effectiveness tests showed a significant improvement in students’ science literacy, with pretest and posttest scores increasing from an average of 45.69 to 81.72 and an N-Gain of 0.68, categorized as medium to high. Improvements were observed across all science literacy dimensions, particularly in scientific attitudes, and the integration of ethno-vlog content enabled students to contextualize ecology concepts within their local cultural environment. These findings confirm that the developed media is valid, practical, and effective, with implications that integrating ethnoscience-based digital media into science instruction can enhance students’ scientific competencies while simultaneously preserving and strengthening cultural identity.